SpaceInk: Making Space for In-Context Annotations - Romat, Hugo; Pietriga, Emmanuel; Henry Riche, Nathalie; Hinckley, Ken; Appert, Caroline (UIST 2019 32nd ACM User Interface Software and Technology Symposium, 2019)
When editing or reviewing a document, people directly overlay ink marks on content. For instance, they underline words, or circle elements in a figure. These overlay marks often accompany in-context annotations in the form of handwritten footnotes and marginalia. People tend to put annotations close to the content that elicited them, but have to compose with the often-limited whitespace. We introduce SpaceInk, a design space of pen+touch techniques that make room for in-context annotations by dynamically reflowing documents. We identify representative techniques in this design space, spanning both new ones and existing ones. We evaluate them in a user study, with results that inform the design of a prototype system. Our system lets users concentrate on capturing fleeting thoughts, streamlining the overall annotation process by enabling the fluid interleaving of space-making gestures with freeform ink.